Biomass and bromatology of African Stargrass (Cynodon nlemfuensis Vanderyst) with five regrowth stages - Ferrufino Suárez, Adriel Jacoc (2022)
Introduction. Establishing the optimal harvest stage of African Stargrass (Cynodon nlemfuensis Vanderyst) is essential to obtain high nutritional quality biomass and maximum productivity. Objective. To evaluate the nutrient production of African Stargrass with five regrowth periods by integrating biomass and nutritional data to establish harvest periods in cut-and-carry systems. Materials and methods. The study was carried out from August through December 2018 at the Dairy Cattle Experimental Station Alfredo Volio Mata (EEAVM), Ochomogo, Cartago. The effect of five regrowth periods (treatments = 7, 14, 21, 28, and 35 days) on the green and dry biomass production, nutritional quality, and effective nutrients production per hectare of African Stargrass was evaluated. The total biomass was measured for each plot, and the nutritional quality was obtained through the contents of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and in vitro dry matter digestibility (IVDMD). The analysis of total effective nutrients production per hectare was performed by integrating nutritional components and biomass production. Results. Fresh and dry biomass increased with increasing regrowth stage. The fresh biomass showed differences greater than 4000.00 kg fresh matter ha-1 per cycle between the highest and lowest treatments. Dry matter yield at 35 days’ regrowth turned out 10 times higher than 7 days’. The crude protein content was greater in treatments with less days of regrowth. No significant differences were found in dry matter, fiber, and digestibility among treatments. Conclusion. The greatest supply of effective nutrients from African Stargrass harvested at 35 days evidenced the importance of integrating biomass and nutritional quality for pasture management under cut-and-carry systems.